(untitled) (Research, Society and Development, 2022)
Violence, regardless of its nature, is one of the two main obstacles to guaranteeing women’s human rights and individual freedom, and affects all stages of life. The objective of the study was to identify cases of violence against women in the state of Acre from 2017 to 2021. It is a cross-sectional, retrospective study with a quantitative approach, whose data collection was carried out at the Information System Department of Single Health (DATASUS). We verified the occurrence of 6,623 cases in the studied period, with a tendency of curfew in the last year. Not that it refers to the age of the victim, most found the age group from 15 to 19 years old 1,838 (28%), followed by the groups from 10 to 14 years old 1,650 (25%) and 20 to 29 years old 1,606 (24%) ). As for the type of violence suffered, the majority was physical violence/spreading, 5,476 (37.4%), sexual violence 3,872 (26.5%), followed by poisoning 1,463 (10.0%) and psychological violence 1,367 (9, 3%). As for the life cycle, the aggressor could not be identified in 4,227 (63.8%) of the cases, as data were not available. Regarding the bond with the aggressor, this data was unidentified in most cases 2201 (33.0%), however among the information possible to be identified, 1374 (20.7%), the violence was committed by the spouse and 936 (14.1%) by the boyfriend. The findings allow the need to implement effective measures that can change the reality in which these women are inserted.